Determinants of non-performing loans in state-owned banks - Renno Prawira; Sudarso Kaderi Wiryono (Jurnal Akuntansi dan Auditing Indonesia)
The increase in NPLs has been shown to have a negative impact on banking sector, so it is highly necessary to consider the determinants of NPLs to ensure the overall economy’s effectiveness and soundness. This study aims to shed light on bank-specific factors affecting NPLs in Indonesia whose banking sector has crucial impacts on the overall economy. The data involved 35 state-owned banks (conventional, Islamic, and regional banks) throughout 2010–2019. The banking factors in this study include bank efficiency, profitability, income diversification, and capital adequacy. Random and fixed effects regression model was used to make the estimates. The results showed that the bank efficiency variable positively correlated with NPLs, but the profitability variable correlated negatively. Both variables were significant statistically, while income diversification and bank capital variables were insignificant statistically. Based on this study, we suggest that the government require banks to have adequate profit. Thus, banks are able to run the good credit management process which will finally decrease the NPLs in the banks.